POTENTIAL POSSIBILITIES OF ENHANCING ONLINE COMMUNICATION OF EDUCATORS IN CONFERENCES - Masami, Yoshida; Thapanee, Thammetar (PEOPLE: International Journal of Social Sciences, 2017)
Communication using Twitter by educators who attended a conference of a centralized position was investigated to better understand the possibility to expand their Twitter communication in the backchannel of the conference. As a target, conferences for ICT educators organized by Ministry of Education, Thailand were selected. Data were collected through an application programming interface (API) by NodeXL, and a social-graph analysis was executed. Extensional investigation was continuously introduced to include personal tweets history of educators by tracing Twitter accounts, which appeared in their profiles as keys of data collection. Results were compared with the findings of preceding studies. The results showed rather inactive Twitter communication of participants during conference days. However, from the result of extensional investigation, integral bridge and hub users, who were expected to enlighten rural educators, were found. Finally, we present three feasible strategies using social group graph analysis that challenged enhancement of awareness regarding the cutting-edge movement in ICT education of rural educators who could not attend a conference. Bridge users were able to forward messages from the conference organizer using deliberate modification of content to adapt their group culture.